The world's great civilizations - Sullivan, Robert, 1953- (New York : Life Books, 2012)
One looks at the pyramids, particularly at tile Great Pyramid and wonders: Who did that? How many did it take? One looks at Stonehenge and wonders: Who? Why? The answers to these and many other questions are in this book.'LIFE' looks at tile civilizations that formed and fomented, not just in the Western world, but all mankind. The Aztecs, the Incas ... But even well before! In what we now know as Iraq, Nebuchadnezzar once ruled, and remnants of his city remain to be pondered. Troy was not fiction, it was real-and remnants remain. What madness possessed the citizenry of Easter Island to seal their own doom? What fate awaited the aboriginal people of Australia when the English arrived? What is the tale of the people of the north, the lnuit'? What about the people of South America-what's the story of those who once worshipped in Machu Picchu? And what about our own country? The Anasazi of the Southwest, ancients even to our Native American tribes, represented a sophisticated society like the world hadn't seen-and then they vanished? What happened to them? This'LIFE' book is full of history and full of mystery, because the world's great civilizations - those of Alexander and Caesar and Henry VIII and George Washington - were incredible, dynamic human societies. Retelling their stories in words and particularly in pictures is a fascinating enterprise.
Introduction: the march of time -- The many cradles of civilzation -- Ancient egypt -- The Babylonian empire -- Ancient Israel -- The Achaemenid empire (Think: Perisia ) -- Greece's Golde Age -- The Macedonian Empire (Think: Alexandr the great ) -- The Roman empires -- The Han Dynasty -- The Maya empire -- The Umayyad caliphate (Think: The Islamic Empire ) -- The Byzantine empire -- The Mongol empire -- The Ming dynasty -- The Inca empire -- The Portuguese empire -- The Ottoman empire -- The Mughal dynasty -- The spanish empire -- The french empires (and Napoleon) -- The Qing Dynasty -- The Russian empire -- The British empire -- Empires of the Axis -- The United states of America -- Just one more.
Keywords: World history -- Pictorial works; Civilization -- Pictorial works; Cities and towns -- History -- Pictorial works